The personality profile of early generative AI adopters: a big five perspective - Anna Kovbasiuk; Tamilla Triantoro; Aleksandra Przegalińska; Konrad Sowa; Leon Ciechanowski; Peter Gloor (Central European Management Journal)
Purpose – This pilot study aimed to evaluate the impact of the big five personality traits on user engagement with chatbots at the early stages of artificial intelligence (AI) adoption. Design/methodology/approach – The pilot study involved 62 participants segmented into two groups to measure variables including engagement duration, task performance and future AI usage intentions. Findings – The findings advocate for the incorporation of psychological principles into technology design to facilitate more tailored and efficient human–AI collaboration. Originality/value – This pilot research study highlights the relationship between the big five personality traits and chatbot usage and provides valuable insights for customizing chatbot development to align with specific user characteristics. This will serve to enhance both user satisfaction and task productivity.